Knowledge of UK Residents About Importing Puppies from EU Countries - Zoe Belshaw; Rowena M. A. Packer (Animals)
The number of puppies imported to the United Kingdom (UK) from the European Union (EU) is increasing, as are concerns about the legality, welfare and potential disease risks associated with their trade. This study aimed to use an online survey to collect questionnaire data from UK residents about their awareness and knowledge of EU Pet Passports, illegal puppy importation, and dog-borne exotic diseases and the risks they might pose to UK-resident dogs and people. Valid responses were collected from n = 7184 UK residents, mainly current dog owners. We identified substantial knowledge gaps relating to EU Pet Passports, how puppies might be moved across Europe, and the legal age of importation. Awareness of exotic diseases was poor; knowledge about the risks they posed was even poorer, particularly in relation to dog–human transmission. With some respondents not even being confident that they had heard of rabies, there is substantial work to do to ensure that the UK canine and human populations remain safe in the face of significant welfare and exotic disease threats. These knowledge deficits may facilitate the burgeoning illegal trade in puppies across the EU. Legal change may be required to prevent consumers from unintentionally supporting poor welfare sources of puppies.